The Talkhis Magza Strategy in Learning Listening Skills for Students - Siregar, Lisa Rahmadhani; Ahkas, Akmal Walad (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2025)
This study aims to explore the effectiveness of the Talkhis Magza strategy in teaching listening skills (maharah istima’) to seventh-grade students at Madrasah Tsanawiyah Swasta Isma’iliyah Aek Loba, Asahan Regency. Talkhis Magza is a learning strategy that emphasizes contextual understanding through listening to audio texts and answering comprehension questions based on interrogative words in Arabic. This research employed a qualitative descriptive method with a field study approach, collecting data through observations, interviews, and documentation. For the results show that this strategy enhances students' ability to comprehend spoken Arabic discourse, increases their concentration and critical thinking skills, and creates a more engaging and interactive learning environment. However, challenges such as limited vocabulary, varying student abilities, and time constraints in lessons serve as inhibiting factors that need attention. And overall, the Talkhis Magza strategy is considered effective in improving students’ listening skills, particularly when supported by adequate learning media and well-structured lesson planning.